Molecular characterization of methicillin-resistant staphylococci from the dairy value chain in two Indian states - Dey, Tushar K.; Shome, B.R.; Bandyopadhyay, S.; Goyal, N.K.; Lundkvist, Å.; Deka, Ram Pratim; Shome, R.; Venugopal, N.; Grace, Delia; Sharma, G.; Rahman, H.; Lindahl, Johanna F. (MDPI, 2023)
Bovine milk and milk products may contain pathogens, antimicrobial resistant bacteria, and antibiotic residues that could harm consumers. We analyzed 282 gram-positive isolates from milk samples from dairy farmers and vendors in Haryana and Assam, India, to assess the prevalence of methicillin-resistant staphylococci using microbiological tests, antibiotic susceptibility testing, and genotyping by PCR. The prevalence of genotypic methicillin resistance in isolates from raw milk samples was 5% [95% confidence interval, CI (3–8)], with 7% [CI (3–10)] in Haryana, in contrast to 2% [CI (0.2–6)] in Assam. The prevalence was the same in isolates from milk samples collected from farmers [5% (n = 6), CI (2–11)] and vendors [5% (n = 7), CI (2–10)]. Methicillin resistance was also observed in 15% of the isolates from pasteurized milk [(n = 3), CI (3–38)]. Two staphylococci harboring a novel mecC gene were identified for the first time in Indian dairy products. The only SCCmec type identified was Type V. The staphylococci with the mecA (n = 11) gene in raw milk were commonly resistant to oxacillin [92%, CI (59–100)] and cefoxitin [74%, CI (39–94)], while the isolates with mecC (n = 2) were resistant to oxacillin (100%) only. All the staphylococci with the mecA (n = 3) gene in pasteurized milk were resistant to both oxacillin and cefoxitin. Our results provided evidence that methicillin-resistant staphylococci occur in dairy products in India with potential public health implications. The state with more intensive dairy systems (Haryana) had higher levels of methicillin-resistant bacteria in milk.